When Religious Leaders Become Marriage Brokers, Penghulus, and Marriage Consultants: The Authority of Kyai in the Process of Unregistered Marriage - Islamiyah, Nanda Nabilah (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2024)
This article attempts to narrate the role played by kyai in the practice of unregistered marriage in Rembang Sub-district, Pasuruan Regency. The kyai's existence was initially built upon the kyai's establishment in carrying doctrines that indicate adherence to religious terms in all actions, including marriage. This article also examines several factors that sustain the kyai profession at three stages of sirri marriage practice: pre-marriage stage, the marriage stage, and the post-marriage stage. This article also discusses the implications of the interaction between the kyai and the clients through the agreement made. The data is generated from interviews with relevant parties who are directly involved in the practice of unregistered marriages. This article finds that the kyai's involvement in the practice of unregistered marriages is shaped by the kyai's power or authority as a marriage broker, marriage official, and sirri marriage consultant. Moreover, the kyai are often relied upon to minimize potential obstacles to marriage, as seen in the case of buying a wali or the practice of wali muhakam. Through the analysis of Weber's theory of authority, the kyais' power softly attracts public sympathy due to their moral and spiritual superiority, which is implemented through their consistency in religious practice and ability to preach. In this way, the community consciously shows obedience to the kyai, thereby narrowing the space for rejection of the kyai's invitation to engage in unregistered marriage practices. [Artikel ini menarasikan bagian peran kyai yang dimainkan dalam praktik perkawinan siri di Kecamatan Rembang, Kabupaten Pasuruan. Eksistensi kyai awalnya dibangun berdasarkan atas kemapanan kyai dalam membawa doktrin yang mengindikasikan kepatuhan terhadap terma agama dalam segala tindakan, termasuk perkawinan. Artikel ini juga mengkaji beberapa faktor yang membuat profesi kyai dapat berlangsung secara kontinu pada tiga tahapan dalam praktik perkawinan siri, yakni tahap pra nikah, tahap perkawinan itu sendiri, dan tahap pasca perkawinan. Artikel ini juga tidak lepas dari pembahasan mengenai implikasi dari adanya interaksi antara kyai dengan para klien melalui kesepakatan yang dilakukan. Data dalam tulisan ini dihasilkan dari proses wawancara dengan pihak yang terlibat secara langsung dalam praktik perkawinan siri. Artikel ini menghasilkan temuan bahwa keterlibatan kyai dalam praktik perkawinan siri terbentuk dari adanya kekuasaan atau otoritas kyai sebagai makelar perkawinan, penghulu perkawinan, dan konsultan perkawinan siri. Selain itu kyai juga dapat diandalkan sebagai pihak yang mampu meminimalisir kemungkinan terjadinya kendala perkawinan, salah satunya ditemukan dalam kasus beli wali atau praktik wali muhakam. Melalui analisis teori otoritas Weber, kekuasaan kyai secara lunak mampu menarik simpati masyarakat sebab keunggulan dalam aspek moral dan spiritual, yang diimplementasikan melalui konsistesi kyai dalam mengaplikasikan amaliyah keagamaan serta kemampuan dalam berdakwah. Dengan cara demikian, secara sadar masyarakat akan menunjukkan kepatuhan kepada kyai sehingga mempersempit ruang penolakan ajakan kyai untuk terlibat dalam praktik perkawinan siri.]